Legal Certainty for Small and Medium Enterprises in Agrarian Regions of South Sulawesi - Alimuddin Alimuddin; Hardiyono Hardiyono; Dian Meiliani Yulis; Ifah Finatry Latiep; A. Resky Fausia Putri (Journal of Entrepreneur, Business and Management, 2026)
Small and medium enterprises operating in agrarian regions depend on land as both a productive asset and collateral, yet a substantial share of that land remains unregistered. This study examines how legal certainty shapes business practice among SMEs in the agrarian districts of South Sulawesi, and identifies the institutional barriers that obstruct it. The study employed an empirical juridical approach combining statutory and conceptual analysis with field data obtained through structured interviews with SME operators, village officials, land agency staff, and cooperative supervisors across three agrarian districts. Data were analysed qualitatively using interactive analysis and triangulated against land administration records and regional regulations. The findings indicate that legal uncertainty for agrarian SMEs originates from three interlocking sources: unregistered land tenure that prevents the conversion of customary and inherited holdings into bankable collateral, fragmented business licensing in which the risk-based licensing regime has not been fully absorbed by district-level implementing units, and weak contractual formalisation in trading relationships between farmers, collectors, and processors. These conditions restrict access to formal credit, weaken bargaining positions in supply chains, and expose businesses to disputes that are resolved informally at considerable cost. The study concludes that legal certainty for agrarian SMEs cannot be achieved through licensing simplification alone, and recommends an integrated approach linking systematic land registration, one-stop licensing assistance at village level, and contract literacy programmes.Keywords: legal certainty; small and medium enterprises; agrarian region; land registration; business licensing.